Influence of the Cyclic Loading Path on Rock Deformation Memory Effect - Lingwei Zhong; Haijun Wang; Xuhua Ren; Lei Tang (Geofluids)
Deformation rate analysis utilizes deformation memory effect (DME) that is one of the fundamental properties of rock, to estimate in situ stress underground. It could be influenced by the stress history which has been subjected to in the past. To understand the influence under the cyclic loading path, in the experimental study, different stress levels were applied on sandstone samples and two types of granite samples. In the theoretical investigation, the sliding friction model consisting of multiple microstructure surfaces is considered in this paper. Both experiments and the theoretical model show that when the number of cyclic loading times keeps increasing, (1) the stress read at the DRA inflection is getting closer to the previously cyclic stress; (2) the angle at the DRA inflection becomes sharper, which gives clearer inflection point; and (3) the strain differential amplitude in the DRA curve gradually decreases and then toward a stable value. An upper limit exists for influence, indicating that the best cyclic loading times occur when the pulse amplitude of the strain differential stops changing. It is confirmed that the multiple cyclic loading method provides a better outcome for experiment using artificial preload when DME is utilized for stress reconstruction. Without other factors disturbing, the memory information of the in situ stress would hardly lose under the history of cyclic loading.